2021
DOI: 10.3390/soilsystems5020023
|View full text |Cite
|
Sign up to set email alerts
|

Drought and Anthropogenic Effects on Acacia Populations: A Case Study from the Hyper-Arid Southern Israel

Abstract: Acacia encompasses a keystone genus across the Middle Eastern and African drylands. This study assesses the dynamics of Acacia populations in two ephemeral stream channels (Nahal Naomi and Nahal Yael) in the hyper-arid Arava region following the establishment of a dam in the upstream channel of Nahal Yael and a long-term regional drought episode. The assessments were conducted at the individual and population levels, for a period of 45 years (during 1972, 1994 and 2017). In Nahal Naomi, the population increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…1b), which could be connected to slightly increasing total precipitation values summed-up over the entire region. Locally, however, the year 2018 cannot be considered particularly humid 40 . Evaporation becomes positive, which means increased condensation and less upward ux from canopy.…”
Section: Resultsmentioning
confidence: 99%
“…1b), which could be connected to slightly increasing total precipitation values summed-up over the entire region. Locally, however, the year 2018 cannot be considered particularly humid 40 . Evaporation becomes positive, which means increased condensation and less upward ux from canopy.…”
Section: Resultsmentioning
confidence: 99%
“…Acacias have also been shown to be susceptible to changes in environmental and ecological conditions, and though in a natural situation the ability for mature specimens to recover following extensive droughts has been demonstrated (e.g. 109 ), the acacia population in Israel has decreased by a third over the last several decades on account of unprecedented exploitation of underground water 48 , 110 , 111 .…”
Section: Discussionmentioning
confidence: 99%
“…This in turn will affect other aspects of the ecosystem, including soil quality and the diversity of faunal species that depend on the acacia and reliant species for forage, shade, and shelter 49 . Acacia are long-lived trees with infrequent periods of recruitment 48,[103][104][105] , with many issues of decreased recruitment in modern contexts especially driven by anthropogenic actions [106][107][108][109] . Acacias have also been shown to be susceptible to changes in environmental and ecological conditions, and though in a natural situation the ability for mature specimens to recover following extensive droughts has been demonstrated (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Acacia populations are affected by climatic changes, and it was demonstrated that the reduction in water availability is related to demographic patterns and mortality rates [29].…”
Section: Discussionmentioning
confidence: 99%
“…Acacia sensu lato (including the genus Vachellia [28]) is defined as a 'keystone genus' due to the significant ecological role in the dryland ecosystems; in fact, these plants influence soil conditions and plant composition [29][30][31][32], but some species developed particular adaptations for survival in extreme arid environments. In addition, the shadow of Acacia trees is essential for the water and energy conservation of several animal and plant species [33][34][35].…”
Section: Introductionmentioning
confidence: 99%